Frequency of Diastolic Dysfunction in Patients With Long-Standing Hypertension Assessed by Clinical and Echocardiographic Parameters - Huma Naeem Tareen, Amjad Ali, Ahsan Iqbal, Muhammad Ali Khawaja, Iftikhar Hussain, Zeeshan Faisal, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Hypertension is a significant healthcare issue on the planet and is one of the primary causes of cardiovascular morbidity and mortality. Prolonged hypertension causes structural and functional changes in the myocardium that causes the impairment of left ventricular relaxation and compliance which results in a diastolic dysfunction. Dysfunction at diastole can be preceded by systolic dysfunction and can go undiagnosed clinically over a long period of time, eventually evolving into heart failure with retained ejection fraction. Echocardiography screening at an early stage is thus required especially in populations where blood pressure has been poorly controlled and where metabolic risk factors are very high. Methods: The study was a descriptive, cross-sectional, study that was carried out in the Department of Cardiology, Lahore Medical and Dental College from 03-01-2023 to 04-07-2023. Non-probability consecutive sampling was used to enroll 180 adult patients who had a history of hypertension lasting five years and above. All the participants were clinically evaluated and underwent a transthoracic echocardiography. The diastolic functioning was measured by the traditional parameters of Doppler and tissue Doppler imaging, and diastolic dysfunction was rated based on the current parameters. The analysis of the data was done using version 26 of SPSS. Results: The age of the participants was 56.8 plus or minus 9.7 years. Sixty-two point two percent of the patients had been found to have diastolic dysfunction. Grade I diastolic dysfunction led the pack with Grade II and Grade III coming in the second and third place respectively. Diastolic dysfunction was more frequent as age advanced, hypertension was not well controlled, and diabetes mellitus. The systolic activity of the left ventricle was preserved in every patient. Conclusion: Diastolic dysfunction has been found to be very common in patients with chronic hypertension and is closely linked with age, years of hypertension and the presence of metabolic comorbidities. It might be possible to detect and promptly intervene in the process of heart failure prevention by having routine echocardiographic evaluation. Keywords: High blood pressure; Left-sided heart failure; Echocardiography; Heart failure and normal ejection fraction.